The Correlation between The Intensity of Broken Home Family Communication and Peer Group Interaction with Adolescent’s Self Concept - Lanty Prabandani; Hedi Pudjo Santoso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2018)
The background of this research is based on many cases of negative self concept in adolescent. Mainly, andolescent from broken home family. Self Concept is related with their sorroundings, such as family and peer groups. This research aims to determine the correlation of the intensity of broken home family communication, peer group interaction, and adolescent ‘s self concept. The method which is used in this research is the quantitative with positivistic approach. This research used The Social Construction Self Theory and The Reference Group Theory. This Research is using non probability sampling technique. The population in this research is adolescent age 17-23 from broken home family in Semarang city. While the sample is 30 respondens. The data is analyzed with the aid of SPSS aplication with Pearson correlation test. The result of this research indicate there is correlation between the intensity of broken home family communication and adolescent ‘s self concept with significance value is 0,004 and Pearson correlation value is 0,511. It means the strength of the intensity of broken home family communication and adolescent ‘s self concept is medium with directional. So, if the intensity of broken home family communication is high, then adolescent’s self concept is high. Otherwise, if the intensity of broken home family communication is low, then adolescent’s self concept is low. And also there is correlation between the peer group interaction and adolescent’s self concept with significance value is 0,041 and Pearson correkation value is 0,375. It means the correlation’s strength is weak and directional. So, if the peer group interaction is high, then adolescent’s self concept is high. Otherwise, if peer group interaction is low, then adolescent’s self concept is low. The suggestion of the researcher is for the parents to improve the intensity of communication with their children, so the children will get knowledge and a good understanding about their self which forming a positive self concept in adolescent.